Design, validation, and application of a hybrid shape memory alloy-magnetorheological fluid-based core bracing system under tension and compression. (January 2022) - Zareie, Shahin; Hamidia, Mohammadjavad; Zabihollah, Abolghassem; Ahmad, Rafiq; Dolatshahi, Kiarash M.
Abstract: Civil infrastructures are vulnerable to catastrophic failures when exceeding the limit loading, requiring a reliable structural control mechanism, such as bracing systems, to enhance the integrity and stability of the structure. Bracing systems improve the performance of the structures by increasing the stiffness/strength of structures, the damping coefficient, and/or the energy absorption capacity. However, the functionality of these bracing systems is not controllable and may be altered after strong seismic events. Recently, the smart bracing systems based on multifunctional materials, particularly the shape memory alloy (SMA) and the magnetorheological fluid (MRF) have been developed. The superelasticity properties of SMA give the capability of recovering the original state after remarkable deformation. Furthermore, the SMA dissipates the energy of the applied load in the loading-unloading mechanism. The viscosity of MRF is variable and depends on the intensity of the applied magnetic fields. In the present study, a state-of-art hybrid SMA-MRF-based core bracing system is designed and in-house fabricated to enhance the structural behavior of the bracing system, including energy dissipation capacity and equivalent damping coefficient. Experimental tests have been conducted to illustrate the functionality of the system and the benefits of the SMA and the MRF systems. Finally, the seismic performance of the three-, six- and nine-story buildings equipped with the proposed SMA-MRF damping system is numerically assessed using nonlinear response history analyses. The results reveal that the proposed damping system significantly improves the seismic performance of the archetype buildings.